Schistosomiasis-associated pulmonary hypertension unveils disrupted murine gut–lung microbiome and reduced endoprotective Caveolin-1/BMPR2 expression - Marinho, Ygor; Villarreal, Elizabeth S.; Aboagye, Sammy Y.; Williams, David L.; Sun, Jun; Silva, Claudia L. M.; Lutz, Sarah E.; Oliveira, Suellen D. (Frontiers in Immunology, 2023)
Abstract: Schistosomiasis-associated Pulmonary Arterial Hypertension (Sch-PAH) is a life-threatening complication of chronic S. mansoni infection, which can evolve into heart failure and death. During PAH, the expansion of apoptosis-resistant endothelial cells (ECs) has been extensively reported, but therapeutic approaches to prevent the progress or reverse this pathological phenotype remain clinically challenging. Previously, we showed that depletion of the anti-apoptotic protein Caveolin-1 (Cav-1) via shedding extracellular vesicles contributes to shifting endoprotective bone morphogenetic protein receptor 2 (BMPR2) towards transforming growth factor beta (TGF-β)-mediated survival of an abnormal EC phenotype. However, what triggered the reduced endoprotection in PAH remained unclear. Interestingly, recent findings indicated that similar to the guts, healthy human lungs are populated by diverse microbiota, with their composition depending significantly on intrinsic and extrinsic host factors, including infection. Despite the current knowledge that disruption of the gut microbiome contributes to the development of PAH, the role of the lung microbiome per se remained widely unclear. Thus, using a pre-clinical animal model of Sch-PAH, we tested whether S. mansoni infection would alter the gut-lung microbiome composition and cause EC injury, initiating the expansion of an abnormal EC phenotype observed in PAH. Indeed, in vivo stimulus with the S. mansoni eggs significantly altered the gut-lung microbiome profile besides promoting injury to the lung vasculature, characterized by increased apoptotic markers and loss of endoprotective expression of lung Cav-1 and BMPR2. Moreover, S. mansoni egg stimulus induced severe pulmonary vascular remodeling, leading to elevated right ventricular systolic pressure and hypertrophy characteristic of PAH. In vitro, exposure to the immunodominant S. mansoni egg antigen p40 activated TLR4/CD14-mediated transient phosphorylation of Cav-1 at residue Tyr14 in human lung microvascular EC (HMVEC-L), culminating in a mild reduction of Cav-1 expression, but failing in promoting death and shedding of extracellular vesicles observed in vivo. Altogether, data suggest that disruption of the host-associated gut-lung microbiota may be essential for the emergence and expansion of the abnormal lung endothelial phenotype observed in PAH, besides the S. mansoni eggs and antigens.